Utility of cfDNA Fragmentation Patterns in Designing the Liquid Biopsy Profiling Panels to Improve Their Sensitivity - Ivanov, Maxim; Chernenko, Polina; Breder, Valery; Laktionov, Konstantin; Rozhavskaya, Ekaterina; Musienko, Sergey; Baranova, Ancha; Mileyko, Vladislav (Frontiers in Genetics, 2019)
Genotyping of cell-free DNA (cfDNA) in plasma samples has the potential to allow noninvasive assessment of tumor biology, avoiding the inherent shortcomings of tissue biopsy. Next Generation Sequencing (NGS), a leading technology for liquid biopsy analysis, continue to be hurdled with several major issues with cfDNA samples, including low cfDNA concentration and high fragmentation. In this study, we performed head-to-head comparison of two amplicon-based NGS panels characterized by a substantial difference in average amplicon length. In course of analysis of the peripheral blood from 13 diagnostic NSCLC patients, equivalence of two panels in terms of overall diagnostic sensitivity and specificity was shown. Regression analysis and EGFR exon 19 deletion calling results demonstrated identical analytical sensitivity in range of 140-170 bp amplicons in size. To increase the sensitivity of mutation detection in cfDNA, we performed computational analysis of the features associated with genome-wide nucleosome maps evident from the data on the prevalence of cfDNA fragments of certain sizes and their fragmentation patterns. By leveraging the machine learning approach, we show that a combination of nucleosome map associated features with GC content results in increased accuracy of prediction of high inter-sample sequencing coverage variation. Thus, nucleosome-guided fragmentation should be utilized as a guide for designing amplicon-based NGS panels for genotyping of cfDNA samples.